Anomalous Temperature Interdicts the Reproductive Activity in Fish: Neuroendocrine Mechanisms of Reproductive Function in Response to Water Temperature - Zahangir, Md. Mahiuddin; Rahman, Mohammad Lutfar; Ando, Hironori (Frontiers in Physiology, 2022)
Fish are poikilotherm and small changes in water temperature can greatly affect physiological processes including reproduction, which is regulated by complex neuroendocrine mechanisms that respond to climatic events. This review provides evidence that anomalous high and low temperature may directly affect reproduction in fish by suppressing the expression of genes in the reproductive neuroendocrine system. The grass puffer, Takifugu alboplumbeus, is an excellent animal model for studying the thermal regulation of reproduction, for they exhibit periodic spawning activities, which are synchronized with seasonal, lunar and daily cycles. In the grass puffer, the expression of the genes encoding gonadotropin-releasing hormone (GnRH) 1, kisspeptin, gonadotropin-inhibitory hormone (GnIH) and their receptors were markedly suppressed in the diencephalon of fish exposed to high temperature (28°C) when compared to normal temperature (21°C), followed by the decrease in the pituitary mRNA levels for follicle-stimulating hormone (FSH), luteinizing hormone (LH) and growth hormone (GH). On the other hand, the exposure to low temperature (14°C) also inhibited the expression of gnrh1, kiss2, gnih and their receptor genes in the brain and fshb, lhb, gh and prl in the pituitary. Taken together, it is plausible that anomalous high and low temperature may be a proximate driver of termination of reproduction by suppressing the activity of the reproductive GnRH/kisspeptin/GnIH system, possibly through direct action of temperature signals at transcription level.